Mycobacterial blood culture for diagnosis of tuberculosis in Vietnamese children - Tran, S; Le, H; Dang, H; Dao, T; Nguyen, L; Nguyen, H; Nguyen, N; Nguyen, N; Thwaites, G; Caws, M; Van Doorn, H; Wertheim, H (Wolters Kluwer Health, 2019)
Diagnosis of pediatric tuberculosis is notoriously difficult. We investigated the additional yield of blood culture in hospitalized children in Vietnam. Among 554 enrolled clinically suspected patients, an additional 6 cases were diagnosed, while the incremental cost per case was USD500. Addition of blood culture is therefore not recommended for our total patient population, but may be considered in specific groups.